Ocorrência e distribuição geográfica da biodiversidade de gafanhotos da subfamília Melanoplinae (Orthoptera: Acrididae) no Brasil. - Santos, Paulo Felipi Lopes dos (Universidade Federal de São Carlos, 2023)
The aim of this study was to review the literature on locust species of the subfamily Melanoplinae (Orthoptera: Acrididae) by collecting secondary data and comparing them with similar studies of locust records. From this survey, tables were prepared in order to present the information of genus, subspecies, species, location, specific coordinates in the Brazilian territory and endemism. Then, maps were made containing the locality of registration of each species, with the intention of analyzing the occurrence of this subfamily in Brazil. Altogether, 15 genera, 104 species and 2 subspecies were recorded, the highest occurrence occurred in the southern, midwestern and southeastern regions. The states with the highest records were Rio Grande do Sul (RS), Mato Grosso (MT) and Minas Gerais (MG), respectively.
Occurrence and geographic distribution of grasshopper biodiversity of the Melanoplinae subfamily (Orthoptera: Acrididae) in Brazil
Keywords: Insecta; Biogeografia; Diversidade; Caelifera; Insecta; Biogeography; Diversity; Caelifera; CIENCIAS BIOLOGICAS::ZOOLOGIA